Nutrigenomic and Biomolecular Aspect of Moringa oleifera Leaf Powder as Supplementation for Stunting Children - Agus Indra Yudhistira Diva Putra; Nyoman Budhi Wirananda Setiawan; Made Indira Dianti Sanjiwani; Ida Ayu Ika Wahyuniari; Agung Wiwiek Indrayani (Journal of Tropical Biodiversity and Biotechnology, 2021)
Stunting is a global health problem. Based on WHO data, there are 161 million children who experience stunting. Breastmilk supplementation in the form of Moringa oleifera leaves powder is known to be beneficial in suppressing the stunting incidence. Moringa oleifera leaves powder contains protein, micronutrients, and minerals such as calcium, iron, sodium, vitamins C and E, beta carotene, and antioxidants (flavonoid acids, phenolic acids, glucosinolates, isothiocyanates, and saponins). The use of Moringa oleifera leaves powder in stunting cases has been carried out, but further studies in the aspects of nutrigenomics and molecular biology have not been conducted. This study is a literature review of relevant articles from www.pubmed.com, www.sciencedirect.com, and scholar.google.com. The author used keywords "stunting", "nutrigenomics", "biomolecular", and "Moringa oleifera". Pathogenic microbe such as Shigella and pathogenic E. coli ingestion can cause changes in DNA sequences in the stunting pathogenesis. Moringa oleifera leave powder can pass through nutrigenomic and biomolecular mechanisms. Some macro and micromolecules of Moringa oleifera leaves powder such as folate plays a role in DNA methylation; vegetable protein and fatty acids act as promoters in DNA sequences; vitamins act as cofactors for enzymes, antioxidant, and antiinflammation. Seeing various potential mechanisms in the aspects of nutrigenomic and molecular biology, Moringa oleifera leaves powder can be used in overcoming stunting. Further research is needed to give more review about cytokines and molecules included in this literature review.